Outcome of Radioiodine Therapy in a West African Population - Yetunde Onimode; Alfred Ankrah; Kayode Adedapo (World Journal of Nuclear Medicine)
Hyperthyroidism continues to be a pressing public health concern in West Africa. Its prevalence in Africa has been quoted as 1.2%-9.9%, with Graves' disease as its most common cause. Radioiodine-131 (RAI) therapy of hyperthyroidism recently commenced in two government hospitals in Ghana and Nigeria. This is a retrospective analysis of consecutive patients treated with RAI for primary hyperthyroidism at the National Centre for Radiotherapy and Nuclear Medicine (NCRNM) from 2008-2013, and in the University College Hospital (UCH) from 2006-2013. Cure was defined as euthyroidism or hypothyroidism occurring at 6 months post-RAI. Data were analysed using SPSS version 21 and Epi Info version, categorical data were evaluated with the Chi-square test and Fisher's exact test. 94 patients were studied, aged 20-74 years; 78 were females, and 16 were males. 38 were Ghanaian and 56 Nigerian. The presence of thyroid-associated ophthalmopathy (TAO) made cure less likely (χ2 P = 0.006, odds ratio = 0.118; 95% confidence interval, 0.027-0.518). Other factors assessed proved to be insignificant. Our findings suggest that hyperthyroid patients with TAO will benefit from a higher RAI dose than their counterparts without TAO.